Erratum: Comparative study of modal dispersion characteristics of different types of concave-lens-shaped dielectric waveguides (Microwave and Opt Technol Lett (2002), 35 (337-342)) - Kumar N.; Srivastava S.K.; Ojha S.P. (My University, 2025)
[No abstract available]